Rethinking age-heaping: A cautionary tale from nineteenth century Italy - Brian A'Hearn; Alexia Delfino; Alessandro Nuvolari (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
A swelling stream of literature employs age-heaping as an indicator of human capital, more specifically of numeracy. We re-examine this connection in light of evidence drawn from nineteenth century Italy: census data, death records, and direct, qualitative evidence on age-awareness and numeracy. Though it can stand in as an acceptable proxy for literacy, our findings suggest that age-heaping is most plausibly interpreted as a broad indicator of cultural and institutional modernisation rather than a measure of cognitive skills.
Keywords: N33; J24; 330; Age-Heaping; Numeracy; Human capital; Italy